1996
DOI: 10.1038/bjc.1996.652
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of TNF-α and melphalan in an isolated limb perfusion model of rat sarcoma: a histopathological, immunohistochemical and electron microscopical study

Abstract: Summary Isolated limb perfusion (ILP) with tumour necrosis factor alpha (TNF-a) and melphalan has shown impressive results in patients with irresectable soft tissue sarcomas and stage III melanoma of the extremities. The mechanisms of the reported in vivo synergistic anti-tumour effects of TNF-a and melphalan are not precisely understood. We have developed an ILP model in the rat using a non-immunogenic sarcoma in which similar in vivo synergy is observed. The aim of this present study was to analyse the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…Moreover, histopathologic observations (Nooijen et al, 1996a) closely resemble observations in patients (Renard et al, 1994;Nooijen et al, 1996b). TNF alone is not active (Posner et al, 1994) and melphalan is only marginally active in soft tissue sarcoma (Kremetz et al, 1977;Klaase et al, 1989), whereas the combination results in very high response rates in this rat model just as in melanoma patients (Liénard et al, 1992;Fraker et al, 1996) or soft tissue sarcoma patients .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Moreover, histopathologic observations (Nooijen et al, 1996a) closely resemble observations in patients (Renard et al, 1994;Nooijen et al, 1996b). TNF alone is not active (Posner et al, 1994) and melphalan is only marginally active in soft tissue sarcoma (Kremetz et al, 1977;Klaase et al, 1989), whereas the combination results in very high response rates in this rat model just as in melanoma patients (Liénard et al, 1992;Fraker et al, 1996) or soft tissue sarcoma patients .…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, a tumour model with a highly aggressive non-immunogenic soft tissue sarcoma in BN rats was developed in our laboratory to address these questions (Manusama et al, 1996). Response after ILP with melphalan and TNF in this model correspond well to what is observed in sarcoma patients in terms of synergy between TNF and melphalan, response rate, and histopathological observations (Manusama et al, 1996;Nooijen et al, 1996a). This rat model could therefore serve as a credible model to study mechanisms and determine ways to optimize ILP efficacy for the clinical setting.…”
mentioning
confidence: 99%
“…These data indicate strongly that in vivo indirect mechanisms mediated by TNF-a in combination with melphalan determine antitumour effects in IHP. Our data support the notion that this indirect mechanism is the selective destructive effect of TNF-a on the tumour-associated vessels, thereby increasing vascular permeability (Nooijen et al, 1996;Ruegg et al, 1998). To investigate this hypothesis, the melphalan uptake in liver and tumour tissue was measured after IHP with or without TNF-a.…”
Section: Discussionsupporting
confidence: 85%
“…In our preclinical ILP model, we observed drastic alterations in tumour microvasculature integrity (Nooijen et al, 1996). Rüegg et al (1998) demonstrated elegantly that TNF-a in combination with IFN-g induced functional downregulation of avb3, resulting in detachment of the endothelial cells of the tumour vasculature.…”
mentioning
confidence: 50%
“…TNF has been known to show marked anticancer effects on certain transplantable tumors [4]. The potential mechanisms of TNF are the vascular changes in tumor tissues [22,30], the modulation of host immunity against tumors [13,24] and the direct cytotoxicity on tumor cells by inducing apoptosis [5,29].…”
mentioning
confidence: 99%